C-reactive protein in drainage fluid as a predictor of anastomotic leakage after elective colorectal resection - Kostić, Zoran; Slavković, Damjan Z; Mijušković, Zoran; Panišić, Marina; Ignjatović, Mile (Vojnosanitetski pregled, 2016)
Background/Aim. C-reactive protein (CRP) is considered to be an indicator of postoperative complications in abdominal surgery. The aim of this study was to determine the significance of serial measurement of CRP in drainage fluid in the detection of anastomotic leakage (AL) in patients with colorectal resection. Methods. CRP values in serum and drainage fluid, respectively, were measured on the first, third, fifth, and seventh postoperative day (POD) in 150 patients with colorectal resection and primary anastomosis. The values obtained were compared between the groups of patient without complications of surgical treatment and those with AL. Results. Clinically evident AL was observed in 15 patients – in two (4.2%) patients with left colonic surgery, and 13 (12.6%) patients with colorectal anastomosis. Mean values of CRP were higher in the patients with AL than in the patients without complications, both in serum and drainage fluid, with the most significant differences recorded on the PODs 5 and 7 (p
Keywords: c-reactive protein; prognosis; surgical wound dehiscence; surgical procedures; operative; colorectal neoplasms